ANALISIS PRODUKSI DAN AGROINDUSTRI KAITANNYA DENGAN PENINGKATAN PENDAPATAN USAHA TANI PISANG AMBON DI PROVINSI SULAWESI SELATAN - Palisuri, Palipada (PERSPEKTIF: JURNAL PENGEMBANGAN SUMBER DAYA INSANI, 2017)
Analysis of Production and Agroindustry of Ambonese Bananas with respect to the Increasing of Farming Income in South Sulawesi Province. This research aimed to ascertain the influence of each production factor on production level of fresh Ambonese bananas, and to know the feasibility of management handling of Ambonese bananas product through household agroindustry activities. The analysis method used were Cobb    Douglass Function and R/C ratio profit analysis. The result of the analysis revealed that the com position of using production inputon the Ambonese bananas farming in Maros and Gowa regency was in the increasing return to scale. Based on the result of statistical test, it could be indicate that the use of seeds was relatively efficien, whereas the use of other production factors were relatively unefficient.  The result of Ambonese bananas sale was relatively profitable as stated by R/C ratio value for 4, 08.